A method for modeling the shock of a rubber buffer with a rigid body - Penkov, Bozhin (Transport, 2008)
The aim of this paper is to introduce a robust methodology for the analytical calculation of acceleration by shock of a rigid body with a rubber buffer. It consists of two stages. At first it is necessary to determine some mechanical properties of the viscoelastic material (rubber) by quasistatic tests. The second stage includes shock testing of a rubber buffer and modeling this process with a theoretical model. The proposed methodology provides good accuracy by comparison of the received experimental and theoretical results.First published online: 27 Oct 2010